6(6m-6)=-8(-4m+5)

Simple and best practice solution for 6(6m-6)=-8(-4m+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(6m-6)=-8(-4m+5) equation:


6(6m-6)=-8(-4m+5)

We simplify the equation to the form, which is simple to understand
6(6m-6)=-8(-4m+5)

Reorder the terms in parentheses
+(+36m-36)=-8*(-4m+5)

Remove unnecessary parentheses
+36m-36=-8+*(-4m+5+)

Reorder the terms in parentheses
+36m-36=+(+32m-40)

Remove unnecessary parentheses
+36m-36=+32m-40

We move all terms containing m to the left and all other terms to the right.
+36m-32m=-40+36

We simplify left and right side of the equation.
+4m=-4

We divide both sides of the equation by 4 to get m.
m=-1

See similar equations:

| -3b-3+9b=-5b-4+11b | | x+5y=-14 | | 3x-10(x+2)=13-17x | | -6y=72 | | 7x-3x=5x+13 | | 6+2(s-5t)= | | 8-(3+7)=7-9 | | -0.25x=-3.4 | | 5(w+3)+3(3w+1)=14 | | 5x+9=-5 | | -10(x-5)=100 | | .75x+.25(10-x)=.59(10) | | 3x-3=2x-9 | | 4x-10y=100 | | 2y+6y=48 | | 3(x+17)=5 | | -120=8x | | 2-3k=10 | | 6x+4+2x=42 | | -4z-7+12z=37-12 | | 6x+6=11x-24 | | 12-x=9 | | 6x+6=-34-4x | | 24=2m | | 2x+[x+3]=24 | | 33.7-(1.5s+2.3)=3.4-(0.4-5.7s) | | 5+4p=-7 | | 5x+4=x+20 | | -6z+4(z+3)=-2z+14 | | 6x+141=5x-3 | | XY+Y= | | -13+13=0 |

Equations solver categories